Transformation of Physics Learning: Integrating Virtual Laboratories to Improve Students' Scientific Literacy Skills - Aziza Anggi Maiyanti; Syamsul Huda; Atika Anggraini; Ummiy Fauziyah Laili; Luthfiyatul Muniroh; Rofiqul Umam (CV FOUNDAE, 2025)
The literacy outcomes of the PISA 2022 test results show that Indonesian students are weak in literacy, suggesting a large gap between the current student performance and the needs of an autonomous curriculated framework. By focus on science literacy viewpoint attitude, this research uses R and D research model, 4D pattern is using to create and validate the module. The purpose of this study is to develop a physics module for teaching that combined with virtual laboratory, to enhance students’ scientific literacy. This study aims to develop a virtual laboratory-based basic physics teaching module, to improve students’ concepts in physics, science literacy of basic physics concepts, and skills. The implementation result support the effectiveness of the module to improve science literacy, and the validation indicates the feasibility of the module. Students' attitude towards science literacy pretest versus posttest assessment significantly different. Summary of this study comprises a more complete teaching tool that it includes modules, videos, and worksheets in a single platform to science literacy. Such findings emphasize that literal experiences need to be mapped on to abstract concepts if literacy is meaningful, and fit with accounts provided by cognitive theory. The pretest and posttest scores of the students produced significant influence on the student’s attitude toward science literacy. According to cognitive theorizing, children must be able to link objects, events, and empirical experiences to develop abstract thinking.